Clinical characteristics and recurrence-related factors of medication-related osteonecrosis of the jaw - Kang, Mong-Hun (J Korean Assoc Oral Maxillofac Surg, 2018)
OBJECTIVES: The purpose of this study was to investigate the demographic and clinical characteristics of patients with medication-related osteonecrosis of the jaw (MRONJ) and to elucidate factors affecting recurrence in surgical treatment. MATERIALS AND METHODS: A total of 51 patients who were diagnosed with MRONJ were analyzed according to demographic and clinical features and treatment results through a retrospective chart review from 2013 to 2017 in the Department of Oral and Maxillofacial Surgery, Korea University Anam Hospital, Seoul in Korea. RESULTS: Alendronate composed the majority of medication doses (55.6%), followed by ibandronate (20.0%), risedronate (15.6%), and zoledronate (6.7%). Forty patients (88.9%) were given oral medication, and five patients (11.1%) were intravenously treated, and the mean duration of medication use was 61.1±42.9 months. A total of 10 patients (22.2%) had a drug holiday before MRONJ-induced dental treatment lasting an average of 6.8±7.0 months. MRONJ occurred 2.7 times more in the mandible, with 41 cases (73.2%) occurring in the mandible and 15 cases (26.8%) occurring in the maxilla, and the prevalence of affected posterior parts (premolar-molar) was six times greater than that of the anterior parts (incisor-canine) (48 cases vs 8 cases, 85.7% vs 14.3%). The most common dental cause of MRONJ was tooth extraction (69.6%). Regarding recurrence, there was no statistical difference in recurrence rate according to either site or stage. However, recurrence occurred in 4 out of 34 cases (11.8%) in the primary closure group and 9 out of 20 cases (45.0%) in the secondary healing group, and there was a statistical difference with respect to closure technique. CONCLUSION: The identified risk factors in patients taking bone resorption inhibitors can aid dental clinicians in ensuring prevention and proper treatment of MRONJ.